Kajian Potensi Air Tanah pada Formasi Vulkanik di Kecamatan Prambanan, Kabupaten Klaten, Jawa Tengah - Erik Febriarta; Septian Vienastra; Gilang Arya Dipayana; Zulfahmi Sitompul; Ajeng Larasati (Jurnal Teknologi Lingkungan, 2022)
The presence of groundwater in volcanic rock formations is generally found in aquifer lithology in the form of loose deposits. The groundwater potential can be obtained by using the resistivity data approach. The purpose of this study was to determine the potential of aquifer parameters in volcanic formations on the middle slope of Mount Merapi in Prambanan District, Klaten Regency. The characteristics and thickness of the aquifer lithology can be determined by using the resistivity data approach which is correlated with rock material. Potential groundwater aquifer parameters were obtained from pump test measurements to determine the value of transmitivity (T) and value of permeability (K). The resistivity value is measured with a value range of 3 –75 ohm m which is interpreted by the aquifer lithology of loose material in the form of sand with fine to coarse grain sizes. The average thickness of the aquifer lithology is 80 m with free aquifer properties. Potential aquifer parameters in the form of transmitivity (T) of 330.6 m2/day and the value of permeability (K) of 8.03 m/day with an average aquifer thickness of 10 m. This value belongs to the category of high aquifer productivity potential.